Effect of high temperature heating on free fatty acid content and peroxide number of packaged and bulk palm cooking oil - Tiara Dia Amanda; M Lutfi Firdaus; Euis Nursaadah; Nurhamidah Nurhamidah; Aceng Ruyani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Palm cooking oil is widely used in food processing, particularly for high-temperature frying. Although the thermal degradation of palm oil has been extensively studied, no previous study has specifically compared the degradation rates of bulk and packaged palm oil under extreme heating conditions. Repeated use at high temperatures may induce chemical changes that affect food safety and public health. This study aimed to analyze the effect of heating on changes in free fatty acid (FFA) levels and peroxide value (PV) in palm cooking oil and assess their implications for food quality. An experimental study was conducted in January 2026 at the Chemistry Education Laboratory, University of Bengkulu, using a factorial design with two main factors: oil type (packaged and bulk) and heating temperature (100, 180, and 200°C). Six repetitions were performed at 10-minute intervals over a total heating duration of 60 min. Data were analyzed using the Shapiro–Wilk normality test and two-way ANOVA in SPSS (version 25). At 200°C after 60 min, the packaged oil showed an increase in FFA to 0.31% and PV to 13.6 meqO₂/kg. Bulk oil exhibited more severe deterioration, with FFA and PV reaching 0.37% and 19 meqO₂/kg, respectively. Temperature significantly affected the increase in FFA (p = 0.000) and PV (p = 0.004) values. In conclusion, both parameters exceeded the national safety standards (SNI) threshold. Limiting the repeated use of heated palm oil is essential for protecting consumer health.